PENERAPAN PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS X-3 MAN 1 PADANG PARIAMAN - Rahma, Puji Aulia; Anggraini, Villia; Melisa, Melisa (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
This research was motivated by the low mathematics learning outcomes of students. The aim of this research is to find out whether students' mathematics learning outcomes after implementing differentiated learning are better than before implementing differentiated learning in class X-3 MAN 1 Padang Pariaman. The type of research used in this research is Pre-Experimental Design research with the design form One-Group Pre-Test Post-Test in one class. The research subject was class X-3. The sampling technique is Purposive Sampling. The instruments used in this research were pre-test and post-test in the form of essays. The data analysis used is hypothesis testing, the Pried Sample T-Test. Based on data analysis from hypothesis testing, t_count = 12.97 and t_tabel = 1.68 with a real level of Î±=0.05, because t_count t_tabel then H_0 is rejected, meaning that students' mathematics learning outcomes after implementing differentiated learning are better than learning outcomes. mathematics students before implementing differentiated learning.